Fodder yeast and biogas production: A fruitful symbiosis? : optimization of a single-cell protein process and examination of its impact on biogas output - Ohlsson, Jonas (SLU/Dept. of Microbiology, 2016)
Due to a growing world population and strained wild fish stocks, aquaculture is expected to provide a large part of the increased global demand for animal protein, as the majority of wild fish stocks are already being fished at or above their sustainable capacity. However, fish feed often contains a significant amount of fish meal, produced from wild-caught fish. Thus, increasing farmed fish production may not be sustainable as long as fish meal remains a major ingredient. Microbial biomass, commonly known as single-cell protein (SCP), can replace fish meal in feed formulations. The financial viability of SCP production is dependent on the availability of cheap growth media. Biogas substrates, often mixtures of waste derived from food industry, agriculture, and households, could be ideal media due to their low cost and ubiquitous availability. The aims of this thesis were: first, to investigate whether yeast SCP can be produced on a biogas substrate consisting of household and agricultural waste; second, to screen several yeast strains and growth conditions for optimal biomass production; and third, to evaluate the effects on biogas production if part of input substrate stream is diverted into SCP production prior to further digestion in the biogas reactor. Several yeast strains were screened for biomass yield at several pH levels and temperatures. After screening, best-performing strains were cultivated on biogas substrate in continuously-stirred bioreactors, analyzing the resultant biomass. Strains were Wickerhamomyces anomalus J121, Pichia kudriavzevii J550, and Blastobotrys adeninivorans J564. Harvested biomass ranged from 7.0–14.8 g dry matter per l substrate, and protein contents were 22.6–32.7 %. Levels of the amino acid lysine were high in all biomass samples, which is important for replacing fish meal in feed formulations. Supernatants from the bioreactor fermentations were combined with whole biogas substrate, and the effects on biogas production were evaluated, as methane produced per g of volatile solids, using a batch methane potential assay. At the highest inclusion levels (1:1 control/supernatant (w/w)) P. kudriavzevii provided an increased output compared to W. anomalus (25 %, p = 0.04). P. kudriavzevii provided a 24% increase compared to control, but results were not significant ( p = 0.06). Filtered, untreated supernatant provided the largest increase in biogas production compared both to control substrate (30 %, p = 0.02) and to W. anomalus (31 %, p = 0.01).